Chronic Kidney Disease of unexplained cause (CKDx): a consensus statement by the Genes & Kidney Working Group of the ERA - Halbritter, Jan Peter; Figueres, Lucile; Van Eerde, Albertien M; Capasso, Giovambattista; Hoorn, Ewout J; Nijenhuis, Tom; Perez-Gomez, Maria Vanessa; Sayer, John A; Simons, Matias; Walsh, Stephen; Zagorec, Nikola; Müller, Roman-Ulrich; et al. (Nephrology, dialysis, transplantation, 2025)
Chronic kidney disease of unexplained cause (CKDx) is a diagnosis of exclusion. With an estimated global prevalence of at least 16-20% among CKD patients, CKDx poses a significant challenge to the field. To date, there is no established consensus on the definition of CKDx. Additionally, guidance on the diagnosis and reporting of CKDx remains lacking. CKDx is characterized by the inability to identify a specific etiology after comprehensive diagnostic evaluation, including laboratory tests, imaging, and histological or genetic analyses. This condition encompasses diverse clinical scenarios, which vary depending on the availability of diagnostic resources across healthcare systems. Notably, as the diagnostic yield of genetic testing in CKDx ranges from 11 to over 30% in the literature, it has become an integral part of the diagnostic armamentarium for patients with CKDx. This consensus statement of the working group ‘Genes&Kidney’ of the European Renal Association proposes a definition of CKDx, along with recommendations for the diagnostic approach and diagnostic reporting standards, including guidance on genetic workup as a key tool in a large proportion of such cases. Improved reporting standards, including the systematic documentation of diagnostic tests performed, are essentialto avoid the negative therapeutic consequences of misdiagnoses, address the diagnostic gap in CKDx, and inform future research. By fostering a cause-directed approach, this work aims to enhance patient care and lay the foundation for further advancements in nephrology.